Morphological Rhythm Structure and Its Phonetic Dimensions in Sūrat Al-Ghāshiyah - sayah, hafed; rahmani, zahreddine (El Omda in Linguistics and Discourse Analysis, 2023)
Abstract : (not more than 10 Lines) The early scholars noticed the morphological rhythmic patterns in the Quran, which were the basis for their naming of the rhymed limits of the verses, i.e. those with the same rhythmic pattern. These rhymed verse limits are stable in both rhythm and meaning and any distorted sound affects the depth of the meaning and the beauty of the structure. Every single surah in the Quran has a specific morphological pattern due to the repetition of rhymed verse limits. Such a feature is prominent in hundreds of morphological and phonetic structures of various types and in various areas. We have selected Surat Al-Ghashiyah, in the last part of the noble Quran. This is because this surah is characterized by specific rhymed verse limits, which give it successive and harmonious morphological rhythmic patterns. This research aims at showing the distinctive structure of the morphological and phonetic rhythmic patterns of Surat Al-Ghashiyah by looking at its rhymed verse limits